The Impact of Mice Multiplier Effect on Local Umkm Income in Medan - Limbong, Elizabet Dos Roulina; Manurung, Susy; Siregar, Yohana Loisa (Maroon Journal De Management, 2025)
This study was conducted to analyze the development of the implementation of MICE (Meetings, Incentives, Conventions, and Exhibitions) activities by contributing to increasing the income of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. This study was conducted with a quantitative approach related to survey techniques on 80 MSME actors who have direct experience in MICE activities. The findings show that most respondents experienced an increase in income and expansion of business relations after their involvement in MICE. Around 80% of respondents have been involved as exhibition booth renters, providers of consumption services, or souvenir makers. Businesses in the culinary and handicraft sectors are the most widely run, because they are in line with the typical needs of MICE events. In addition to providing a direct economic impact, MICE has also proven to be a strategic promotional media for local MSME products. However, there are still various obstacles such as limited production capacity, lack of mastery of digital technology, and minimal training available. Thus, synergy between MSME actors, event organizers, and the government is key to optimizing the role of the MICE industry as a driver of local economic growth.